Consumer buying behavior of luxury branded good / Darel Nicol Luna Anak Agam… [et al.] - Agam, Darel Nicol Luna; Usin @ Husin, Ymma Fatzrin (2013)
Consumers make many buying decisions every day decisions are the focal point of a marketer’s effort. Marketing stimuli consist of four Ps, which are product, price, place, and promotion. Consumer purchases are strongly influenced by cultural, social, personal, and psychological characteristics (Azuma & Femie, 2003). The luxury sector targets its products and services at consumers at the top-end of the wealth spectrum (Mansharamani & Khanna, 2008). These self-selected elites are more or less price-insensitive and choose to spend their time and money on objects that are plainly opulence rather than necessities (Mansharamani & Khanna, 2008). For these reasons, luxury and prestige brands have for centuries commanded an unwavering and often illogical customer loyalty. In general, luxury goods are highly priced products often in the niche market of goods. Individuals purchase these goods for different purposes. These could include a diamond engagement ring, a Louis Vuitton bag for self-reward, an expensive car to match the neighbor’s BMW, or a luxury brand of headband called Sereni & Shentel, a luxury product which was chosen for this research and will be further explained in the background of study.